The Use of Lidocaine Containing Cardioplegia in Surgery for Adult Acquired Heart Disease. Issue 9 (22nd July 2015) - Yammine, Maroun; Neely, Robert C.; Loberman, Dan; Rajab, Taufiek Konrad; Grewal, Amardeep; McGurk, Siobhan; Fitzgerald, Daniel; Aranki, Sary F.
ABSTRACT Background Del Nido cardioplegia, a crystalloid‐based solution with lidocaine as a key element, is given as a single dose and has been used successfully in congenital cardiac surgery. Hypothesis We retrospectively compared a lidocaine containing "modified del Nido" solution with our standard whole blood cardioplegia to investigate its safety and efficacy in adult cardiac surgery. Methods From June 1, 2013 to December 30, 2013, we used a single dose of lidocaine containing cardioplegia (LC group) in 92 consecutive operations. Propensity matching analysis was undertaken to compare the outcomes of such patients with those who underwent their surgery by the same surgeon using standard whole blood cardioplegia (WB group), n = 396. Propensity score matching yielded 79 pairs of patients. Results After propensity matching, LC and WB groups were similar in baseline operative characteristics including cross‐clamp time (LC: 65 minutes [range 54 to 89] vs. WB: 70 minutes [54 to 86], p = 0.993). Postoperative outcomes were similar including inotropic requirements (30.4% [24/72] vs. 25.3% [20/72], p < 0.60), median ventilation time (4.7 hours vs. 5.3, p < 0.74) and median length of stay was seven days for both groups (p < 0.82). Despite higher median postoperative, 24‐hour CK‐MB levels LC group (LC:22.3 ng/ml, range [15.6 to 40.3] vs. WB:18.4 ng/ml [13.9 to 28.2], p = 0.040), operative and one‐year mortality were comparable among study groups (both p > 0.798). Conclusions Lidocaine containing cardioplegia appears to be safe in adults undergoing cardiac procedure when administered for the first 60 minutes of aortic cross clamping. Higher CK‐MB levels did not translate into adverse clinical outcomes. doi: 10.1111/jocs.12597 (J Card Surg 2015;30:677–684)